solve (3-4i) (6i+7) - (2-3i)
show solving steps-- picture is provided.
![solve 34i 6i7 23ishow solving steps picture is provided class=](https://us-static.z-dn.net/files/d61/3de612e70010d134ebbb2b5689d4886e.png)
Answer:
-7 i + 43
Step-by-step explanation:
Simplify the following:
(-4 i + 3) (6 i + 7) - (-3 i + 2)
(3 - 4 i) (7 + 6 i) = 3×7 + 3×6 i - 4 i×7 - 4 i×6 i = 21 + 18 i - 28 i + 24 = 45 - 10 i:
(-10 i + 45) - (-3 i + 2)
-(-3 i + 2) = 3 i - 2:
45 - 10 i + (3 i - 2)
45 - 10 i - 2 + 3 i = (45 - 2) + (-10 i + 3 i) = 43 - 7 i:
Answer: -7 i + 43